Biodegradability under marine conditions of bio-based and petroleum-based polymers as substitutes of conventional microparticles. (December 2022) - Cheng, Jingguang; Eyheraguibel, Boris; Jacquin, Justine; Pujo-Pay, Mireille; Conan, Pascal; Barbe, Valérie; Hoypierres, Julia; Deligey, Gaëlle; Halle, Alexandra Ter; Bruzaud, Stéphane; Ghiglione, Jean-François; Meistertzheim, Anne-Leila
Highlights: The biodegradation of 7 polymers in the marine environment was investigated to challenge their application as potential substitutes of the conventional microbeads used in cosmetics and personal care products. Innovative 2-stepwise experiments were designed to mimic realistic natural conditions. The four biodegradation steps were characterized, including biodeterioration, biofragmentation, bioassimilation and mineralization. The biosourced PHBV is proposed as the best biodegradable polymer tested to replace the conventional microbeads. Abstract: Plastic microbeads have been produced at very large scales since several decades for cosmetics and personal care products, a large amount of which is being directly transported in the oceans. To better understand their biodegradability in marine environment and evaluate their possible replacement by biodegradable polymers, seven polymer types were studied including three conventional petroleum-based polymers (PE, PMMA, and PCL), two bio-based polymers (PLA and PHBV), and two natural products (rice seeds and apricot kernel). We used several innovative approaches by both the experimental design and the set of multidisciplinary techniques to follow the successive steps of biodegradation together with abiotic degradation under seawater conditions. Congruent signs of biodegradability were observed by oxygen consumption, weight loss, and modification of molecular weight, 1 H NMR, and mass spectrometry profiles. We found that microparticles made of PHBV, PCL, rice, and to a lesser extent apricot were biodegradable under our conditions, while not microparticles made of PE, PMMA, and PLA. Taking into consideration of the industrial application, PHBV could be the potential material to replace the conventional microbeads, since the material is resistant to hydrolysis, but susceptible to microbial degradation, as shown by the 1 H NMR results. This study provides the first time arguments for the use of biodegradable substitutes to replace conventional microbeads to support the recent legislative rules aiming to reduce the pollution by primary microplastics in the oceans. Graphical abstract: Image, graphical abstract